2001
DOI: 10.2166/hydro.2001.0002
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall-runoff modelling using adaptive neuro-fuzzy systems

Abstract: Two important applications of rainfall-runoff models are forecasting and simulation. At present, rainfall-runoff models based on artificial intelligence methods are built basically for short-term forecasting purposes and these models are not very effective for simulation purposes. This study explores the applicability and effectiveness of adaptive neuro-fuzzy-system-based rainfall-runoff models for both forecasting and simulation. For this purpose, an adaptive neuro-fuzzy system with autoregressive exogenous i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 5 publications
0
17
0
1
Order By: Relevance
“…The neuro-fuzzy system, the so-called ANFIS approach, was proposed by Jang (1993). It has been applied successfully to various hydrological problems, such as streamflow predictions (Gautam & Holz, 2001) and reservoir operations . Figure 1 illustrates the structure of the basic fuzzy inference system, which consists of four functional blocks, such as the fuzzy rule base, a fuzzifier, a fuzzy inference engine and a defuzzifier.…”
Section: Methodsmentioning
confidence: 99%
“…The neuro-fuzzy system, the so-called ANFIS approach, was proposed by Jang (1993). It has been applied successfully to various hydrological problems, such as streamflow predictions (Gautam & Holz, 2001) and reservoir operations . Figure 1 illustrates the structure of the basic fuzzy inference system, which consists of four functional blocks, such as the fuzzy rule base, a fuzzifier, a fuzzy inference engine and a defuzzifier.…”
Section: Methodsmentioning
confidence: 99%
“…Block-box modelling to simulate the rainfall-runoff relationship has been investigated extensively (for 25 example, Shamseldin and O'connor, 1999;Gautam and Holz, 2001;Talei et al, 2010). These models are fast and the results are often comparable with physical models.…”
Section: Relationship Between Rainfall and Water-level At Gauging Sitesmentioning
confidence: 99%
“…The advantage of using a neuro-fuzzy approach to develop a data modeling is the possibility to obtain a model that results not only accurate but also interpretable (Plantamura et al 2003). Moreover, the neuro-fuzzy approaches have been also used by (Gautam et al 2003;Nazemi et al 2004) for rainfall-runoff modeling. They reported that this technique effectives to increase the rainfall-runoff models for both forecasting and simulation.…”
Section: However Climate Fluctuation Of the Tropical Pacificmentioning
confidence: 99%